Factores del proyecto de Desarrollo Agrícola Rural (DAR) Callahuanca que han contribuido para que la población de Barbablanca y Callahuanca, puedan superar los impactos negativos del desastre natural y mejoren su calidad de vida, en el periodo 2018 - 2021 - Rojas Arana, Emma Lizeth (2024)
In 2017, due to the intense rains caused by the Coastal El Niño Phenomenon, mudslides and stones affected the valley and devastated much of the population of Barbablanca. In response to this situation, energy generation company Enel implemented the Rural Agricultural Development Project (DAR) Callahuanca, which took place from 2018 to 2023 with the objective of improving the technical, commercial, and associative capacities of the population to enhance their agricultural economic activities and thereby increase their economic income. The objective of this research is to understand the factors of the DAR Callahuanca project that have contributed to the population of Barbablanca and Callahuanca overcoming the negative impacts of the natural disaster and improving their quality of life in the period 2018 - 2021. To this end, the research presents three findings: 1. Improvement in quality of life (through agriculture and natural resource care – environmental sustainability), 2. Vulnerability, collaboration, and associativity, and 3. Disaster prevention and linkage to Plans, Policies, or Programs. As part of the research, primary information was collected through interviews and focus groups with members of the DAR Callahuanca project, non-participating population, local authorities, and companies executing the project such as Enel and Forestar. A thorough review of secondary information was also conducted to develop the contextual framework based on geographic and demographic information, physical, economic, and productive aspects of the locality, employment, agriculture, tourism, health, housing, and basic services, development index, and climate crisis. From a regulatory aspect, the research refers to national and international regulations with a special focus on the environmental sector; and in the theoretical framework, the research is oriented towards territorial development, capacity development, equality, discrimination and vulnerability, crisis, and climate change. This research significantly contributes to the knowledge in social management by analyzing the effectiveness of a post-disaster development project and examining its capacity to achieve sustainable population development. Its findings and recommendations not only enrich the field of social management by providing empirical evidence and contextualized analysis on the response to natural disasters but also offer practical tools to social managers and public policy makers for planning and managing future rural projects in similarly high-vulnerability contexts. Furthermore, this study underscores the importance of disaster prevention and effective linkage with policies and programs at the local and national levels, establishing a valuable precedent by demonstrating how the integration of sustainable agricultural practices and the promotion of social cohesion can strengthen community resilience and foster inclusive and sustainable economic development. In this sense, the results of the study not only have theoretical and methodological implications but also offer clear guidelines for the implementation of initiatives that enhance adaptation and mitigation capacity in the face of future disasters, thus contributing to the construction of more resilient and equitable societies.